정보주체 보호를 위한 사이버보험 의무 가입 필요성에 관한 연구 - 홍준호; 강주영 (원광법학, 35(1), 2019)
정보통신기술의 발달의 역기능으로 대량의 개인정보가 유출되는 사고가 전세계적으로 빈번하게 발생하고 있다. 그런데 개인정보유출 사건의 경우 개인정보가 침해된 정보주체는 피해액에 대한 입증이 어렵고 소송절차 또한 번거로우며 그 배상액 또한 낮다는 문제점이 있다. 또한 해킹 등으로 인하여 개인정보 유출을 당한 기업은 그 손해배상의 범위가 확정되어 있지 않기 때문에 손해배상액을 예측하는 것이 어려워 위험관리에 대한 어려움이 있다. 이러한 위험 관리 차원에서 미국에서는 “사이버 배상책임보험”(Cyber Liability Insurance:CLI)이 도입되었다. 사이버배상책임보험은 e-비즈니스, 네트워크 및 정보 자산 등 사이버 위험과 관련하여 계약당사자의 위험 뿐 아니라 제3자에 대한 손해배상 문제까지 모두 담보하는 보험을 의미하는데, 기업이 개인정보유출로 인한 위험을 관리할 수 있도록 돕고 정보주체에게는 확실한 손해배상을 담보해준다. 국내에서도 개인정보유출사고에서 피해자에 대한 배상책임을 담보하는 보험인 사이버 배상책임보험의 일종으로 일부 손해보험회사에서 “개인정보보호배상책임보험”이 제공되어 왔으나 이용실적은 미미하였다. 그러던 중에 국내에서 발생한 개인정보 유출사고, 예컨대 2011년 7월 SK커뮤니케이션즈(3500만 여명), 2012년 KT(870만건), 2014년 1월 KB국민, NH농협, 롯데카드 등 3개 신용카드사(1억 580만 건)의 대규모 개인정보 유출사고를 계기로 개인정보 유출의 심각성과 그 배상방법의 불확실성에 대한 우려가 확대되면서 개인정보유출시 배상보험 가입의 의무화 법안들이 국회에 의원입법으로 상정되어 왔다. 「신용정보의 이용 및 보호에 관한 법률」은 2015년 3월 11일에 보험가입 의무화 규정(제43조의3)이 신설되었고 최근 「정보통신망 이용촉진 및 정보보호 등에 관한 법률」도 보험가입 의무화 규정이 신설되었다. 본 연구에서는 개인정보유출배상책임보험의 가입 의무화에 관한 주제를 가지고 사이버보험이 필요한 이유를 살펴보고자 한다. 개인정보유출 및 손해배상 현황과 현재 국내외 사이버보험 현황을 살펴본 후에 제도적으로 사이버보험이 필요한 이유를 살펴보고자 한다. Accidents caused by a large amount of personal information leaked out frequently due to functional impairment of information and communication technology all over the world. However, in the case of personal information leakage cases, it is difficult for the information entity whose personal information has been infringed to prove the amount of damage, the procedure is also troublesome and its compensation is low. In addition, companies that received leakage of personal information due to hacking etc. have not confirmed the extent of damages due to leakage, it is difficult to predict the amount of damages by this, and there is difficulty for risk management. Cyber ​​liability insurance (CLI) was introduced in the United States and others at these risk management levels. Cyber ​​liability insurance is an insurance covering all risks of contracting parties and damages against third parties in relation to cyber risk such as e-business, Internet network and information assets, To manage the risks of the outflow of the victims to ensure the certainty of damages to the victims. In Japan as well, insurance that guarantees liability for victims in connection with the leakage of personal information is a type of cyber liability insurance and has been provided as insurance products under the name "personal information protection liability insurance" at multiple insurance companies However, the usage record was insignificant. Under such circumstances, for example, SK Communications (35 million people), 2012 KT (8.7 million cases) in July 2011, KB citizen, NH Agricultural Cooperative, The concern over the seriousness of the leakage of personal information and the uncertainty of the method of compensation expands with the three large credit card companies (105.8 million) of the Lotte Card caused by the massive personal information leakage accident, A bill to oblige insurance to participate in information leakage has been supposed in the Diet by lawmakers. The law on the use and protection of credit information is based on the provision of insurance coverage obligation provisions (Article 43-3) on March 11, 2015, and the law concerning the promotion of the use of information and communication networks and information protection as well as the insurance policy obligation provision Was newly established. In this research, I would like to see why cyber insurance is necessary with a topic on mandating subscription obligation for information leakage liability insurance. I would like to see the reason why cyber insurance is required institutionally after investigating the current status of personal information leakage and damages compensation and the current situation of domestic and international cyber insurance. KCI Citation Count: 7